Analisis Faktor-Faktor yang Mempengaruhi Minat Menggunakan Financial Technology Syariah pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Thaha Saifuddin Jambi - Rian Ade Saputra; M. Nazori; Efni Anita (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
In today’s modern era, humans have a life with endless activities and technological developments that is currently maturing in indonesia is financial Technology. Financial Technology (fintech) is the latest innovation in the financial service system which is touched by modern technology, to make it easier for people to make payments, investments, borrow money, transfer money and so on. The problem formulation for this (1) do usability factors influence students’interest in using sharia fintech (2) can trust factors influence students’interest using sharia fintech (3) can risk factors influence students’interest using sharia fintech. The aim of this reseacrh is to look at the backround of the problem is to find out the factors that influence interest using sharia fintech at UIN STS Jambi. Based on the result of previous research, the following conclusions can be conveyed in this research (1) The result of the research show that partially the perception of usefulness is not influence in mintst using financial technology with a significance value of 0.103. (2) The research results show that partially trust has no effect on interest in using Financial technology with significance value of 0.060/ (3) The research results show that partially risk has an effect on interest in using financial Technology with a significance value of 0.000 (4) base on the test results, it is known that the value reaches 116.391, while the significance value is 0.000. this shows that perceived usefulness of trust and risk influence interest in using Financial Technology